Application of Journalistic Ethics in Political Reporting in Online Media (Case Study of the Governor Election of Jakarta) - Santoso, Didik Haryadi (Jurnal Pekommas, 2018)
The selection of the Governor and Deputy Governor of DKI Jakarta in 2017 have been completed. There are several problems in the contestation, especially those relating to violations of journalistic ethics in political reporting in online media. Two key questions in this research, first, what is the form of violations of journalistic ethics in the political reporting of the Jakarta Governor’s election in national online media during 2016-2017? Second, how journalistic ethics to the political reporting of the Jakarta governor's election in national online media in 2016-2017? This study uses a qualitative approach with Robert K. Yin's case study method with national online media research subjects including sindonews.com, mediaindonesia.com, kompas.com, republika.co.id and tribunnews.com. The results of this study, there are several violations of journalistic ethics, besides the application of journalistic ethics in online media in the selection of the Governor of DKI Jakarta is not optimal. The causes are economic and political factors.